Trade potential under the SAFTA between India and other SAARC countries: the augmented gravity model approach - Vipin Sharma; Vinod Kumar (Statistics in Transition New Series, 2021)
The study attempts to analyse India's trade potential with other SAARC member states under the SAFTA agreement by means of the augmented gravity model, at annual frequency from 1992 to 2019 in general and from 2004 to 2019 in particular. The findings of this paper prove that the intra-regional trade volumes between SAARC countries can be increased and encouraged. Moreover, the research shows that it is important to introduce structural reforms aiming to boost trade with non-member states. It would be advisable for researchers to take into account the effect locational and infrastructural advantages have on transport costs through the application of a gravity model. Previous research has also demonstrated that the augmented gravity model may prove helpful in explaining some key features of South Asian trade, which traditional gravity models fail to do.
Keywords: 519; Cooperation/integration; augmented gravity model; panel data; trade potential; SAARC; SAPTA; SAFTA